中国企业跨国经营中竞争策略研究 = The competitive strategy study of chinese enterprises oversea operation - 聂卫东 Nie, Weidong (2008)
This paper gives an analysis to the current development and the main causes of the difficulty in transnational operations. In the meantime, this paper has a fuller investigate of the Group’s operation environment, advantages and disadvantages. This paper also gives some policy and strategy recommendations at different levels.